Gangguan Penyulang Akibat Kegagalan Proteksi di Circuit Breaker Output Pelanggan Pada Gardu Distribusi MP 244 - Setyanto, Muhammad Rifqi; Saragih, Yuliarman (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2023)
The distribution network requires a protection system so that the electric power is distributed optimally using CBO cubicles (Output Circuit Breakers). the differencese with general cubicles are additional devices in the form of Circuit Breakers or PMT, Current Transformers (CT), Potential Transformers (PT), and relays. CBO installation is important to minimize disturbance to the feeder. Medium Voltage Network has spindle, mesh, and radial configuration. The MP 244 substation is also equipped with Ground Fault Detection (GFD) which functions as a short circuit fault detector to the ground and to speed up localizing interference on 20 kV. Maintenance of medium voltage distribution networks is divided into replacement, predictive, preventive, and corrective maintenance. Meanwhile, in the maintenance of the 20kV cubicle, PLN officers must also follow various stages regulated in certain SOPs. The aim of the research is to maintain the 20 kV cubicle in the medium voltage distribution network based on the applicable SOP so that protection failures at the MP 244 distribution substation do not recur. Keyword— Circuit Breaker Output (CBO); Ground Fault Detector (GFD); Network; Corona; Cubicles 20kV; Medium Voltage